2019
DOI: 10.1002/jcb.29127
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 is involved in sevoflurane‐induced neurotoxicity in developing rats

Abstract: Objective The purpose of this study is to uncover the effects of long chain noncoding RNA (lncRNA) metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) on sevoflurane‐induced neurotoxicity in developing rats. Methods Sevoflurane neurotoxicity model was established by sevoflurane treatment in 7‐day‐old Sprague‐Dawley rats. The rats were treated with Sevo or MALAT1 small interfering RNA to detect the MALAT1 expression, pathological change, ultrastructure, neuronal apoptosis, expression of apoptosis‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Hence, our findings may provide new insights into the pathogenesis of sevoflurane-related neurotoxicity. Our findings, together with facts that sevoflurane exposure significantly up-regulated lncRNA Gadd45a expression and lncRNA HOTAIR in rat hippocampus [25,36], but down-regulated LncRNA Malat1 expression in infant rats [37], suggest that different lncRNAs may have varying functions and form a network in regulating the sevoflurane-related neurotoxicity against NSCs. This regulatory network will determine the self-renewal and differentiation of NSCs.…”
Section: Plos Onementioning
confidence: 59%
“…Hence, our findings may provide new insights into the pathogenesis of sevoflurane-related neurotoxicity. Our findings, together with facts that sevoflurane exposure significantly up-regulated lncRNA Gadd45a expression and lncRNA HOTAIR in rat hippocampus [25,36], but down-regulated LncRNA Malat1 expression in infant rats [37], suggest that different lncRNAs may have varying functions and form a network in regulating the sevoflurane-related neurotoxicity against NSCs. This regulatory network will determine the self-renewal and differentiation of NSCs.…”
Section: Plos Onementioning
confidence: 59%
“…LncRNAs are involved in the pathology of brain tumors, including glioma [ 38 ]. Moreover, lncRNA-mediated networks are responsible for understanding the activity of Sev [ 10 ], such as lncRNA metastasis-associated lung adenocarcinoma transcript 1 and small nucleolar RNA host gene 1 [ 39 , 40 ]. Here we were the first to confirm HMMR-AS1 was decreased via Sev in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNAs are another class of ncRNAs, recent studies have identified many paradigms that illustrate how lncRNAs function, including targeting proteins to specific genomic location to affect transcription patterns, modulating the activity of protein-binding partners and serving as precursors for small RNAs ( Wilusz et al, 2009 ). A recent study in 2018 uncovered the effects of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) on sevoflurane-induced neurotoxicity in developing rats ( Hu et al, 2019 ). It demonstrated that rats anesthetized with sevoflurane show the high expression of MALAT1, the downregulation of BDNF and NGF mRNA and protein levels, the increase of neuron apoptosis and pathological structural changes in hippocampus and the impairment of spatial learning and memory ability.…”
Section: Non-coding Rnamentioning
confidence: 99%